The Influence Of Financial Literacy On The Effectiveness Of Village Fund Management In Tompobulu District, Gowa Regency - Vira Prithy Fani; Nasrullah, Nasrullah; Abd. Khaliq (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a type of quantitative research with the aim of determining the influence of financial literacy on the effectiveness of village fund management in Tompobulu District, Gowa Regency. The type of data used is quantitative analysis with data collection through observation and questionnaires using data collection techniques: validity and reliability tests, classical assumption tests and simple regression analysis. The research results that can be written show that financial literacy for the t count of 6,489 is greater than the t table of 1,691 (6,489 > 1,691) has a significant effect on the effectiveness of village fund management. Based on the results of research conducted at the data collection, data management and data analysis stages regarding the influence of financial literacy on the effectiveness of village fund management in Tompobulu District, Gowa Regency, it can be concluded that financial literacy has a positive and significant effect on the effectiveness of village fund management in Tompobulu District, Gowa Regency.